2014
DOI: 10.1001/jamaophthalmol.2013.6077
|View full text |Cite
|
Sign up to set email alerts
|

Merkel Cell Carcinoma of the Eyelid

Abstract: IMPORTANCE The literature on Merkel cell carcinoma (MCC) of the eyelid remains scarce, and there has yet to be a study using the most up-to-date TNM staging system for this rare but aggressive tumor. OBJECTIVE To analyze the TNM stage, management, and outcomes of patients with MCC of the eyelid. DESIGN, SETTING, AND PARTICIPANTS Retrospective case series of 21 patients from 5 tertiary referral centers in the United Kingdom and Australia with primary MCC of the eyelid presenting at a median age of 77 years, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 53 publications
2
35
0
1
Order By: Relevance
“…This was found to be negative [ 27 ]. Herbert et al [ 28 ] reported performance of a SLNB in just 1 patient of their 21. Tumor size at presentation was <1 cm, and the results of SNLB were negative.…”
Section: Discussionmentioning
confidence: 99%
“…This was found to be negative [ 27 ]. Herbert et al [ 28 ] reported performance of a SLNB in just 1 patient of their 21. Tumor size at presentation was <1 cm, and the results of SNLB were negative.…”
Section: Discussionmentioning
confidence: 99%
“…Given that, depending on the location, recommended surgical margins of 2 cm are often not feasible during the primary excision, microscopically controlled surgery is a valuable, tissue-sparing procedure allowing for complete resection in the periorbital region [10]. Subsequently, special plastic-reconstructive surgery procedures are required.…”
Section: Commentsmentioning
confidence: 99%
“…MCC is more commonly identified in the upper eyelid and usually arises near the eyelid margin, often causing partial or complete eyelash loss [9,16,19,20]. The typical appearance is that of a violacious, rapidly growing mass lesion associated with soft tissue ulceration, destruction, and eyelash loss (Figure 1).…”
Section: Merkel Cell Carcinoma Of the Eyelidmentioning
confidence: 99%
“…While eyelid and periocular lesions may present earlier due to better visualization of the lesion in this location, MCC of the head and neck still demonstrates high incidence of spread to the regional lymph nodes with up to 2/3 of patients having regional lymph node metastasis and 1/3 of patients with distant metastasis within 18 months of diagnosis [9,16,19]. MCC of the eyelid has been reported to have an overall metastatic rate ranging from 10% to 30% [16,19,20], regional lymph node recurrence rate of 20%, and distant metastasis rate of 5% [20]. The recent study by our group demonstrated a 22% metastatic rate overall which included an 11% nodal metastasis and 11% distant metastasis rate [22].…”
Section: Prognosismentioning
confidence: 99%